2014
DOI: 10.1002/jmri.24694
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐parametric (mp) MRI of prostatic ductal adenocarcinoma

Abstract: Although DCa mimics Gleason score 3 + 3 = 6 tumor at T2W MRI; DCa resembles Gleason ≥7 CCa on mp-MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Wibner et al [21] have previously demonstrated the utility of ADC-derived textural parameters in TZ tumour detection and differentiating grade based on lesion analysis. The textural analysis approach may obviate previously described efforts to normalise by using ADC ratios (normalized to non-tumorous tissues) [22], perform whole lesion measurement and/or generate histogram analysis including median and low percentile ADC values [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Wibner et al [21] have previously demonstrated the utility of ADC-derived textural parameters in TZ tumour detection and differentiating grade based on lesion analysis. The textural analysis approach may obviate previously described efforts to normalise by using ADC ratios (normalized to non-tumorous tissues) [22], perform whole lesion measurement and/or generate histogram analysis including median and low percentile ADC values [23]. …”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of DCa at needle biopsy requires definitive therapy and is considered an absolute contraindication for AS [ 55 , 56 ]. Schieda et al recently demonstrated that DCa is of increased SI on T2W MRI, which can render the tumour occult [ 39 ]; however, the same authors demonstrated that DCa resembles Gleason score ≥7 or higher tumour on DWI and DCE [ 57 ]. Therefore, in a lesion with aggressive imaging findings on DWI/DCE and paradoxical increased T2W SI, DCa should be considered [ 57 ] (Fig.…”
Section: Interpretive Pitfallsmentioning
confidence: 99%
“…different scanner systems, different b-values) challenge the translation of these findings to clinical practice. Moreover, there is debate about the methodology and reproducibility of ADC measurements with the recent description of ADC ratios (normalized to non-tumorous tissues) [17], whole lesion measurement and histogram analysis including median and low percentile ADC values [18]. More advanced methods of image processing and analysis may be a next step to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%